EFEKTIVITAS INTEGRASI MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA DENGAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN DI KABUPATEN BADUNG PROVINSI BALI - Mahajaya, Ida Bagus Krisdeny; Yasa, I Nyoman Mahaendra; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.02.TAHUN 2018DO - 10.24843/EEB.2018.v07.i02.p05, 2018)
This study to analyze (1) the effectiveness of the integration program rural development planning with community empowerment national program of rural self-sufficient in the Badung regency of Bali Province; (2) the effect of the implementation of the integration program rural development planning with the national community empowerment program in rural independently on household income target in the Badung regency of Bali Province; (3) the effect of the implementation of the integration program rural development planning with community empowerment national program on employment in rural independent target households in the Badung regency of Bali province. The results showed (1) the effectiveness of the integration program rural development planning with the national community empowerment program in rural independent in the Badung regency of Bali Province effective with the achievement of values ??above 80 percent; (2) The implementation of the integration program rural development planning with national community empowerment program in rural independent positive and significant impact on household income target in the Badung regency of Bali Province; (3) The implementation of the integration program rural development planning with national community empowerment program in rural independent positive and significant impact on employment for the target households in the Badung regency of Bali province.